Draft Annual Plan 2000-2001 Volume II Statements I to VII Excluding Statements III Which is in Supplement of Volume II Government of Uttar Pradesh - Planning Commission (Planning Commission, 2000)
Summary Statement of Major Head wise - Outlays and Expenditure Sub-Major Head wise - Outlays and Expenditure, Physical Targets & Achievements A Externally Aided Projects - Outlays and Expenditure Externally Aided Projects - Physical Targets and Achievements Basic Minimum Services - Outlays and Expenditure Basic Minimum Services - Physical Targets and Achievements Centrally Sponsored Schemes - Outlays and Expenditure District Plan - Outlays and Expenditure.
Government of Uttar Pradesh, State Planning Commission